2015
DOI: 10.1371/journal.pone.0125674
|View full text |Cite
|
Sign up to set email alerts
|

Does Reproductive Investment Decrease Telomere Length in Menidia menidia?

Abstract: Given finite resources, intense investment in one life history trait is expected to reduce investment in others. Although telomere length appears to be strongly tied to age in many taxa, telomere maintenance requires energy. We therefore hypothesize that telomere maintenance may trade off against other life history characters. We used natural variation in laboratory populations of Atlantic silversides (Menidia menidia) to study the relationship between growth, fecundity, life expectancy, and relative telomere … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 51 publications
1
26
0
Order By: Relevance
“…As telomere length and erosion appear to be adaptive, there is reason to expect they may mediate trade-offs between developmental life-history processes and longevity [64]. Intriguingly, several animal models provide support for this line of thinking [65][66][67][68][69][70]. In addition, then, to early-lifeadversity effects on telomere regulation, the energetically costly process of reproduction can further impact the rate of aging via accelerated telomere erosion, thereby supplying the second hit of our model.…”
Section: Hit Twomentioning
confidence: 72%
“…As telomere length and erosion appear to be adaptive, there is reason to expect they may mediate trade-offs between developmental life-history processes and longevity [64]. Intriguingly, several animal models provide support for this line of thinking [65][66][67][68][69][70]. In addition, then, to early-lifeadversity effects on telomere regulation, the energetically costly process of reproduction can further impact the rate of aging via accelerated telomere erosion, thereby supplying the second hit of our model.…”
Section: Hit Twomentioning
confidence: 72%
“…Consequently, if telomeres are biomarkers of reproductive output, the selective pressures acting on them could be sex dependent, which has indeed been shown . Some studies reported significant effects only in one sex, whereas others ignored one sex (males) completely . Discussing sex differences should also attract more attention because in some populations males and females display divergent telomere erosion patterns and losing telomeres may bring about sex‐specific consequences.…”
Section: Studies Published To Date Have Many Limitationsmentioning
confidence: 99%
“…As a control single-copy gene we used the melanocortin 1 receptor with the primers specific for guppies, MC1R-F (5′-GTCCTCGCTCTCCTTCCTGT-3′) and MC1R-R (5′-CACACCACCGCGATGATGGT-3′). We chose to use MC1R, because it is a single copy gene in many teleost species (Selz et al, 2007) and it has already been used in Menidia menidia for RTL calculation (Gao & Munch, 2015). Furthermore, the mapping of Relative telomere length was obtained following the equation proposed by Pfaffl (Pfaffl, 2001) to 100 ± 20%.…”
Section: Relative Telomere Length Measurementmentioning
confidence: 99%